Effect of sugar cane straw ash (SCSA) as solid precursor and the alkaline activator composition on alkali-activated binders based on blast furnace slag (BFS) - Moraes, J. C.B. [UNESP]; Tashima, M. M. [UNESP]; Akasaki, J. L. [UNESP]; Melges, J. L.P. [UNESP]; Monzó, J.; Borrachero, M. V.; Soriano, L.; Payá, J. (Elsevier, 2017)
Alkali-activated materials (AAM) comprise one of the solutions to diminish the use of Portland cement in building construction and, consequently, a reduction in the environmental problems related to CO2 emissions and energy consumption may be achieved. These kinds of binders are obtained when a mineral precursor (calcium silicate or aluminosilicate material) is mixed with an alkaline solution. In this study, the blast furnace slag (BFS) combined with a new waste from the sugar cane industry, sugar cane straw ash (SCSA), is utilised. This new residue was studied replacing partially the blast furnace slag in BFS/SCSA proportions of 100/0, 85/15, 75/25, 67/33 and 50/50. The alkaline solution concentration plays an important role in obtaining AAM with good mechanical properties. Therefore, this paper intends to assess the influence of the activating solution (composed of sodium hydroxide and sodium silicate) through different H2O/Na2O (called η) and SiO2/Na2O (called ε) molar ratios. For BFS/SCSA proportions of 100/0 and 75/25, the η values assessed were 22, 28 and 37, whereas the ε values selected were 0 and 0.75. In order to study the effects of SCSA in the mixture, other BFS/SCSA proportions (0–50% replacement) were assessed by only η and ε ratios of 28 and 0–0.75, respectively. To reach these objectives, mortars and pastes were manufactured in order to study their behaviour in the following testscompressive strength (3, 7, 28 and 90 days of curing at 25 °C), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray diffraction (XRD), mercury intrusion porosimetry (MIP) and field emission scanning electron microscopy (FESEM). The results showed that the alkaline solution influenced the compressive strength development, and specimens reached more than 60 MPa after 90 days of curing. In addition, the mortars with SCSA and without sodium silicate presented similar values of compressive strength to those samples with only BFS and sodium silicate, showing that the ash can replace the sodium silicate, which is the pollutant and an expensive chemical reagent, yielding a sustainable binder. Therefore, SCSA presented good results and is a promising material in alkali-activated binders.
Keywords: Biomass waste; Compressive strength; Environmentally friendly material; Microstructural studies; Sustainability